2018
DOI: 10.2147/dhps.s178394
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors predicting drug-induced liver injury due to flucloxacillin

Abstract: ObjectivesDrug-induced liver injury (DILI) is a serious adverse reaction due to flucloxacillin. The pathogenesis is not fully understood. Female sex, age over 60 years, and a longer treatment duration have been suggested to be predisposing factors. Carriers of HLA-B*57:01 have an 80-fold increased risk, but due to the rarity of the reaction, testing of all patients is not cost-effective. We aimed to validate and detect clinical risk factors for flucloxacillin DILI.MethodsClinical characteristics of flucloxacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For ulipristal acetate, it was due to the structural features shared with telapristone acetate [49] and onapristone [50], which had been demonstrated to be idiosyncratic. Flucloxacillin HLA-B*57:01 is indicated as a clinical risk factor for idiosyncratic DILI [47]. However, the DNN model identified only fasiglifam and flucloxacillin as DILI-positives; the DILI properties of the two drugs might arise from their structures, although there has been no supportive report in that regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ulipristal acetate, it was due to the structural features shared with telapristone acetate [49] and onapristone [50], which had been demonstrated to be idiosyncratic. Flucloxacillin HLA-B*57:01 is indicated as a clinical risk factor for idiosyncratic DILI [47]. However, the DNN model identified only fasiglifam and flucloxacillin as DILI-positives; the DILI properties of the two drugs might arise from their structures, although there has been no supportive report in that regard.…”
Section: Discussionmentioning
confidence: 99%
“…Although they had various indications, the DILI test results demonstrated that, except for ulipristal acetate and ligandrol, all drugs were predicted correctly as DILI-positives with a mean accuracy of 0.867. In particular, three of the 15 drugs, namely, fasiglifam, ulipristal acetate [46], and flucloxacillin [47], showed liabilities for idiosyncratic DILI. Fasiglifam was suggested to be idiosyncratic due to the delayed increase in alanine aminotransferase in some patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that in general the incidence of hypokalaemia and associated hospitalization is higher among females 1,11–14 . Females are also more at risk for other flucloxacillin‐induced adverse events, including drug‐induced liver injury and metabolic acidosis 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…1,[11][12][13][14] Females are also more at risk for other flucloxacillin-induced adverse events, including drug-induced liver injury and metabolic acidosis. 15,16 Considering the limited knowledge about the incidence, risk factors and potential influence of sex on flucloxacillin-induced hypokalaemia, a retrospective cohort study was performed. The primary aim of this study was to determine the incidence of flucloxacillininduced hypokalaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are considered the most commonly implicated drug category in idiosyncratic DILI development ( Katarey and Verma, 2016 ; Björnsson, 2017 ). Flucloxacillin and co-amoxiclav are well-tolerated beta-lactam penicillins and widely used in clinical practice with an acceptable safety profile; however, they have been reported to cause DILI ( Donati et al, 2017 ; Lindh et al, 2018 ; Teixeira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%